Assessing Water Use, Energy Use And Carbon Emissions In Lift‐ Irrigated Areas: A Case Study From Karshi Steppe In Uzbekistan†. (3rd February 2019) - Djumaboev, Kakhramon; Yuldashev, Tulkun; Holmatov, Bunyod; Gafurov, Zafar
Abstract: The advantages of a nexus approach in addressing complex environmental challenges are becoming increasingly clear. In Central Asia, however, the nexus between water–food–energy has not received adequate attention, as the very few studies that have been conducted fell short of quantifying nexus trade‐offs and benefits at a practical, small scale. This paper applies a quantitative accounting method to assess water and energy use intensity in irrigated areas of the Karshi Steppe of Central Asia that are supplied by pumping water uphill (lift‐irrigated) from the underlying river. The results indicated that the potential water and energy savings as well as the greenhouse gas (GHG) emission reductions could be achieved by applying an optimal planning deficit irrigation schedule simulated using CROPWAT 8. Some 575 MCM (million cubic metres) of water and 259 GWh of electricity can be saved, while the CO2 equivalent emissions can be reduced by almost 122 000 t. Achieving these savings requires a mix of technical and policy components. This paper describes an example of proper irrigation planning as a tool for water/energy savings and consequent reduction of CO2 emissions. © 2019 John Wiley & Sons, Ltd. Résumé: Les avantages d'une approche par lien pour résoudre des problèmes environnementaux complexes deviennent de plus en plus évidents. En Asie centrale, toutefois, le lien entre eau, nourriture et énergie n'a pas fait l'objet d'une attention suffisante, car les très rares études menées n'ont pas permis de quantifier les compromis et les avantages du lien à une petite échelle. Ce papier applique une méthode de comptabilité quantitative pour évaluer l'intensité d'utilisation de l'eau et de l'énergie dans les zones irriguées de la steppe de Karshi en Asie centrale alimentées par le pompage d'eau en amont (irrigué par élévation d'eau) à partir du fleuve sous‐jacent. Les résultats ont indiqué que les économies potentielles d'eau et d'énergie ainsi que les réductions d'émissions de gaz à effet de serre (GES) pourraient être réalisées en appliquant un calendrier optimal d'irrigation déficitaire simulé avec CROPWAT 8. Quelque 575 MCM (millions de mètres cubes) d'eau et 259 GWh d'électricité peuvent être économisés, tandis que les émissions d'équivalent CO2 peuvent être réduites de près de 122 000 t. La réalisation de ces économies nécessite un mélange de composants techniques et politiques. Ce papier décrit un exemple de planification appropriée de l'irrigation en tant qu'outil permettant d'économiser de l'eau/de l'énergie et, par conséquent, de réduire les émissions de CO2 . © 2019 John Wiley & Sons, Ltd.